Are Teachers in Africa Poorly Paid? Evidence from 15 Countries - Evans, David K.; Yuan, Fei; Filmer, Deon (World Bank, Washington, DC, 2020)
Pay levels for public sector workers—and especially teachers—are a constant source of controversy. In many countries in Sub-Saharan Africa, protests and strikes suggest that pay is low, while simple comparisons to average national income per capita suggest that it is high. This study presents data on teacher pay from 15 African countries, along with five comparator countries from other regions. The results suggest that in several (seven) countries, teachers' monthly salaries are lower than other formal sector workers with comparable levels of education and experience. However, in all of those countries, teachers report working significantly fewer hours than other workers, so that their hourly wage is higher. Teachers who report fewer hours are no more likely to report holding a second job, although teachers overall are nearly two times more likely to hold a second job than other workers. With higher national incomes, the absolute value of teacher salaries rises, but they fall as a percentage of income per capita. The study explores variation across types of teacher contracts, the association between teacher pay and student performance, and the association between teacher pay premia and other aspects of economies.